Heterocyclic Molecular Targeted Drugs and Nanomedicines for Cancer: Recent Advances and Challenges - Junxia Liu; Tengfei Chao; Yingying Liu; Chen Gong; Yinan Zhang; Huihua Xiong (MDPI AG, 2023)
Cancer is a top global public health concern. At present, molecular targeted therapy has emerged as one of the main therapies for cancer, with high efficacy and safety. The medical world continues to struggle with the development of efficient, extremely selective, and low-toxicity anticancer medications. Heterocyclic scaffolds based on the molecular structure of tumor therapeutic targets are widely used in anticancer drug design. In addition, a revolution in medicine has been brought on by the quick advancement of nanotechnology. Many nanomedicines have taken targeted cancer therapy to a new level. In this review, we highlight heterocyclic molecular-targeted drugs as well as heterocyclic-associated nanomedicines in cancer.